THE INFLUENCE OF THE AVAILABILITY OF NON-HALAL RESTAURANTS AROUND CAMPUS ON STUDENTS' DECISIONS IN CHOOSING HALAL FOOD (CASE STUDY AT THE BEKASI STIAMI INSTITUTE) - Sutandi; Anton Bawono (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This research aims to analyze the influence of non-halal restaurants around the Bekasi STIAMI Institute campus on students' decisions to choose halal food. In a campus environment dominated by non-halal restaurants, students face limited access to and choices for halal food. This research uses a quantitative method with a questionnaire instrument to evaluate students' perceptions of two main factors: the existence of non-halal restaurants (X1) and the offer of halal food (X2). The research results show that the presence of non-halal restaurants significantly affects students' preference for halal food, with an R value of 0.729 and an R Square of 0.531. Despite this influence, religious factors remain dominant in shaping students' preferences, supported by considerations of accessibility, price, and variety of halal food. In conclusion, students prioritize consuming halal food even when more diverse non-halal options are available around the campus. Therefore, improving the accessibility and variety of halal food options around the campus is essential to better meeting the needs of Muslim students.